Thriving on chaos : handbook for a management revolution - Peters, Thomas (Harper Perennial, 1987)
Tom Peters describes forty-five tactics for bringing about a revolution in how companies are managed. The author maintains that this revolution is crucial to economic survival in the face of constantly changing conditions, such as new technologies, rapid fluctuations in currencies, disappearance of the mass market, and the proliferation in competitors.